Health Communication: Family Counseling as a Cooperation Strategy for Handling Stunting Problems in Pamoyanan District, Bogor City - Rofi’ah, Rofi’ah; Hamidah, Rizka Nur; Sa’diyah, Maemunah; Rahman, Imas Kania; Fauzan, Muhammad Rifki (Universitas Ibn Khaldun Bogor, 2024)
Indonesian Ministry of Health states that there has been a decrease in the stunting rate in Indonesia, however, based on WHO health standards, the stunting rate in Indonesia is still high. This fact shows that posyandu as the spearhead of handling stunting still needs to develop strategies in an effort to reduce stunting rates. This research analyzes the intervention strategies carried out by posyandu cadres in the Pamoyanan sub-district, in implementing health communication for handling stunted children. The findings of this research are that the family counseling health communication intervention pattern in the form of mutual cooperation in handling stunted children by the entire family of the stunted child has proven to be effective in restoring the health of the stunted child, where the whole family works together to implement a healthy eating pattern for the stunted child. This research also found that assigning treatment only to mothers proved to be less effective, in addition to the characteristics of highly educated mothers not always producing a parenting pattern that could prevent stunting in children. This research is qualitative research with a case study approach on five stunted children found in the Pamoyanan sub-district.